Systematic Review of Socio-Emotional Values Within Organizations - Pascucci, Tancredi; Cardella, Giuseppina Maria; Hernández-Sánchez, Brizeida; Sánchez-García, Jose C. (Frontiers in Psychology, 2022)
The theory of separation assumes, with provocation, that an organization cannot reconcile profits and social function. Organizations can reconcile these two, apparently contrasting, missions, by considering emotions, especially moral emotions, to create a genuine motivation for focusing on goals beyond simple economic earnings and protecting organizations or groups of people from dysfunctional attitudes and behaviors, as well as considering the important role of the stakeholder accountability. Using the PRISMA method, we created a review of records using keywords relating to a socio-emotional value within organizations, with a particular focus on the last 20 years. We used the SCOPUS database and, after removing irrelevant records, we used the VOSviewer tool to create a cluster map of different areas in this topic. Some records cite the socio-emotional value that is related to organizational and employee suffering, while other articles consider it a positive factor that improves performance and prevents problems in organizations.